Characterisation of the arsenic resistance genes in Bacillus sp. UWC isolated from maturing fly ash acid mine drainage neutralised solids - Wicleffe Musingarimi; Marla Tuffin; Donald Cowan (South African Journal of Science)
An arsenic resistant Bacillus sp. UWC was isolated from fly ash acid mine drainage (FA-AMD) neutralised solids. A genomic library was prepared and screened in an arsenic sensitive mutant Escherichia coli strain for the presence of arsenic resistance (ars) genes. Sequence analysis of a clone conferring resistance to both sodium arsenite and sodium arsenate revealed homologues to the arsR (regulatory repressor), arsB (membrane located arsenite pump), arsC (arsenate reductase), arsD (second regulatory repressor and a metallochaperone) and arsA (ATPase) genes from known arsenic resistance operons. The Bacillus sp. UWC arsRBCDA genes were shown to be arranged in an unusual manner with the arsDA genes immediately downstream of arsC.